The virtual and real representation of architecture Photography: changes and standstills - Cianci, Maria Grazia (DISEGNARECON, 2013)
Photography has always been and will always be the most efficient tool used to capture, freeze and crystalize reality. Digital photography, including the graphical and technological instruments needed to achieve it, allows us to intervene in a dynamic manner on the “static” image. Photography and the analytical technologies are used to represent realities on which we can intervene: they freeze reality and stop changes from occurring. Reality is frozen to represent itself and the subsequent gestural intervention as to create a “change” that isn’t linked to the figurative aspects of the pictures but rather to the dynamic reality. The union of these two processes generates “new” images: an idea is added to reality to imagine the way it should be represented. This contribution illustrates these processes.